Penerapan Asuhan Berpusat pada Perempuan dalam Asuhan Kebidanan Berkelanjutan Nyonya S di Puskesmas Sewon 1 Bantul - Rana Dhiya Fadhilah; Eka Nur Rahayu; Riadini Wahyu Utami (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
ABSTRACTMaternal and child health is a problem in Indonesia and even the world. It is proven in the Sustainable Development Goals (SDG's), one of the goals in the health sector is to improve the welfare of mothers and children. In addition, according to the Indonesian Ministry of Health in 2015, the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) each year reached 450 per hundred thousand live births. However, this can still be prevented by providing appropriate and intensive care to the client. One of the intensive care is comprehensive care. Comprehensive midwifery care if done properly can prevent or detect early complications that will occur in the mother. The client is Mrs. S, she has one risk, which is over 35 years old, so it is a risky pregnancy. Midwives in the case of midwifery students provide comprehensive midwifery care. Students are able to apply continuous midwifery care from pregnancy to the puerperium to Ny. S at Sewon 1 Health Center Bantul. The care provided during pregnancy is pregnancy massage because Mrs. S several times complained of fatigue. During childbirth the author provides care by teaching the mother breathing relaxation techniques and motivating the mother. During the postpartum period, the mother was worried because her breast milk had not yet come out, so she was given oxytocin massage and motivation for the mother. During the neonatal period, Mrs. S had experienced jaundice, the care provided was to breastfeed the baby to the mother and recommended breastfeeding at least every 2 hours even though the milk had not come out. Continuing midwifery care has been provided to Mrs. S by taking into account the various risk factors that Mrs. S and the baby. Keywords: Continuity of Care, Pregnancy Massage, Oxytocin Massage